Neutrophil-to-lymphocyte ratio in predicting neurologic outcome of patients with acute ischemic stroke treated with intravenous thrombolytics. Issue 1 (6th August 2021) - Chen, Chung-Ting; Li, Li-Hua; Su, Pei-Ying; Chang, Yu-Chin; Lee, I-Hui; Yen, David Hung-Tsang; How, Chorng-Kuang
Abstract : Background: Recombinant tissue plasminogen activator (rtPA) is currently the most standard treatment for patients with acute ischemic stroke (AIS). However, rtPA treatment may further enhance the immune response poststroke. This study is to investigate the clinical utility of white blood–based inflammatory biomarkers in predicting neurologic outcomes among AIS patients receiving rtPA. Methods: A retrospective observational cohort study of 100 patients with AIS treated with intravenous rtPA was conducted in an urban tertiary hospital in Taiwan. Favorable neurological outcome defined as modified Rankin Scale (mRS) score 0 to 2 in poststroke follow-up was the primary outcome measure. Baseline and post-rtPA neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) were investigated for potential predictors. Results: These patients had a mean age of 71.3 ± 13.7 years and the average of initial National Institute of Health Stroke Scale was 12.7 ± 6.5. Using multiple regression analysis, PLR was not an independent factor; however, both baseline and post-rtPA NLR were independent factors predicting favorable neurological outcome at 3, 6, 12 months after a stroke. The area under the receiver operating characteristic curve for baseline and post-rtPA NLR were 0.645 (95% confidence interval [CI], 0.537-0.753) and 0.769 (95% CI, 0.676-0.862) ( Z score = 2.086) in 3-month, 0.645 (95% CI, 0.537-0.752) and 0.791 (95% CI, 0.701-0.880) ( Z score = 2.471) in 6-month, and 0.646 (95% CI, 0.538-0.754) and 0.813 (95% CI, 0.728-0.898) ( Z score = 2.857) in 12-month poststroke follow-up. Conclusion: For AIS patients treated with rtPA, both lower baseline and post-rtPA NLR levels were independently associated with a favorable neurologic outcome in serial mid- and long-term follow-up. Post-rtPA NLR was superior to baseline NLR in discriminative performance for neurologic prognosis.